Pengelolaan Sarana dan Prasarana Pendidikan Dalam Meningkatkan Kualitas Pendidikan Mahasiswa Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Palangka Raya - Bernisa Bernisa; Dedy Norsandi; Yossita Wisman (FKIP Universitas Palangka Raya, 2024)
This investigation aims finding out about the management of educational infrastructure and amenities in the Faculty of Social Sciences Of Palangkaraya. The focus of this research is quality improvement. The goal of this study is to find out the management of infrastructure and facilities for education. This research uses a qualitative use a descriptive tack when approaching. The data a source for this study was based on conversations with the Head of Study Program, students and cleaning staff. The discussion's conclusions obtained from this study are to improve the level of instruction with good infrastructure and facilities management in education. The description of the discussion obtained, namely; (1) The Role of Infrastructure and facilities for education. (2) Distribution of Educational Infrastructure and Facilities. (3) Utilization of Educational Infrastructure and Facilities. The conclusion from this discussion is the importance of managing infrastructure and educational facilities to improve the effectiveness of learning quality.